2021
DOI: 10.5195/ijt.2021.6365
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Patients in Cardiac Rehabilitation Programs: A Multicenter Randomized Controlled Trial

Abstract: Concerns have been raised about motivation and psychological distress when implementing telerehabilitation in patients with heart failure. The current study compared conventional and telerehabilitation in two groups (n=67; n=70) of patients with heart failure at 0, 6, and 12 months on measures of motivation (Self-Determination Theory measures) and psychological distress (Hospital Anxiety and Depression scale). We found no significant changes in motivation across groups, although our telerehabilitation group ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The fact that our TR group felt more motivated to use digital services indicate that the FPT program may have successfully motivated patients to use the digital telerehabilitation platform, as they engaged in using relevant digital health services. As such, these findings supports the notion that when designing telerehabilitation programs, it is important to create digital health services that motivate and match the needs of the users in order to give them a positive user experience ( 25 ). Simply digitalizing existing services is not sufficient for successful engagement in telerehabilitation, motivation is essential for digital practices becoming a routine part of the patients’ everyday lives, in turn improving disease management and self-care.…”
Section: Discussionsupporting
confidence: 74%
“…The fact that our TR group felt more motivated to use digital services indicate that the FPT program may have successfully motivated patients to use the digital telerehabilitation platform, as they engaged in using relevant digital health services. As such, these findings supports the notion that when designing telerehabilitation programs, it is important to create digital health services that motivate and match the needs of the users in order to give them a positive user experience ( 25 ). Simply digitalizing existing services is not sufficient for successful engagement in telerehabilitation, motivation is essential for digital practices becoming a routine part of the patients’ everyday lives, in turn improving disease management and self-care.…”
Section: Discussionsupporting
confidence: 74%
“…24 This proposition is supported by a study that examined motivation in patients participating in cardiac telerehabilitation versus traditional CR, which found that the traditional CR group was more likely to be dependent on external sources of motivation, such as health personnel, compared with the telerehabilitation group. 47 This study has several limitations. Given the observational study design, cause and effect could not be implied.…”
Section: Discussionmentioning
confidence: 92%
“…Remote methods of CR delivery may have been more appealing to those who were already self-motivated to exercise, whereas in-person sessions were preferred by patients who needed more support because of closer and direct instruction, guidance, and supervision 24. This proposition is supported by a study that examined motivation in patients participating in cardiac telerehabilitation versus traditional CR, which found that the traditional CR group was more likely to be dependent on external sources of motivation, such as health personnel, compared with the telerehabilitation group 47…”
Section: Discussionmentioning
confidence: 96%
“…Rehabilitation programs often include educational components that help patients understand the importance of regular exercise and strategies for coping with motivational difficulties. In addition, group exercise sessions can provide social support and a sense of community, which also positively affects patient engagement [17,18].…”
Section: The Importance Of Motivation and Psychological Supportmentioning
confidence: 99%